CHARTER OF THE STAVROPOL KRAI: PROBLEM ISSUES AND SEARCH FOR SOLUTION - V. Cherepanov (Гуманитарные и юридические исследования)
The Charter of the Stavropol Krai, being an integral part of the constitutional legislation of Russia, is intended to carry out legal regulation of the most important public relations of constitutional signiicance. The Territorial Charter adopted in 1994 underwent signiicant changes as a result of the introduction of numerous amendments, dictated by sometimes not by real problems, but by short-term political interests. The current edition has a large number of gaps, does not regulate many public relations of constitutional signiicance, and is largely a formal and declarative document. As a result, a real contradiction between the actual social relations of constitutional signiicance and the provisions of the Charter has been arisen, though the Charter is called upon to exercise their rightful regulation, but has not properly performed this most important constitutional function. The author has proposed the conceptual approach that has been embodied in the Model Draft of the Charter of the Stavropol Krai, which has been posted on the new informational portal "Constitutional-Legal Forum" for broad discussion by the scientific and expert community. The conceptual approach underlying the Model Draft assumes that the Territorial Charter must have at least ive basic legal properties: a constitutive character; fundamental character; direct action; legal supremacy in the regional legal system; stability. The article highlights the problematic issues that have arisen during the statutory regulation (in terms of the selected legal properties of the Charter), identiies permissible solutions and the possibility of their legislative implementation in the text of the new Charter of the Stavropol Krai. The interpretation of the source of the government of the Stavropol Krai, which is the people of the Stavropol Kraias part of the multinational people of the Russian Federation, has been proposed. The necessity of a signiicant array of statutory rules that have direct effect with a minimum number of reference provisions has been substantiated; the main ones have been considered in the context of the chapters of the Model Draft of the Charter. The arguments in favor of the creation of the Charter Court of the Stavropol Kraihave been presented, new regulations to ensure the stability of the Charter of the Stavropol Kraihave been proposed. The proposal to organize a discussion on a new Charter of the Stavropol Kraihas been made.